Comparison of the European Union Member States in the Field of Social Insurance in the Period 2007-2019 - Jarmila Rybová; Iveta Sekničková (European Financial and Accounting Journal, 2022)
The article aims to compare the Member States of the European Union in the field of social insurance over the selected period. In this context, it is necessary to identify the trend of changes in the period 2007-2019. The article answers two questions. First, whether there is a growth in the share of social insurance in the tax systems or not. The second question concerns the approximation of the Member States in the field of social insurance. The Eurostat database is a source of indicators that represent social insurance in the tax system of the individual Member States of the European Union. We used Ward's method of cluster analysis to evaluate the annual results. Three indicators are subject to cluster analysis. The result of our work comprises four groups of the Member States of the European Union. Each group consists of similar states. Our results confirm that the country's historical position and traditions influence the established social insurance system. The European Union law ensures social security coordination. It mainly affects migrants.
Keywords: H22; H24; 650; Social Insurance; Tax System; European Union